A new technique for examining intestinal biopsies. Issue 11 (November 1973) - Chapman, B. L.; Henry, K.; Paice, F.; Stewart, J. S.; Coghill, N. F.
Abstract : A new technique for measuring changes in the architecture of the small intestinal mucosa is described using a modification of the technique of television image analysis to measure the areas occupied by the surface and crypt epithelium in proximal jejunal biopsies. The ratios of these two areas to each other were then calculated. In 12 control mucosae, the mean ratio (±SD) was 2·27 ± 0·41. In 12 untreated flat mucosae, by contrast, the mean ratio was only 0·24 ± 0·07. This ten-fold difference, which was highly significant (p < 0·001), was greater than that for any similar measurements previously reported. This technique is intended for the measurement of changes in the mucosa too small for existing techniques to detect reliably rather than for the diagnosis of coeliac disease.